The Effect of a Combination of Foot Exercises and Warm Water Soaks on Improving Peripheral Circulation in Patients with Diabetic Neuropathy - Nelly Emilia Wulandari; Anis Ika Nur Rohmah (Jurnal Kesehatan Metro Sai Wawai, 2026)
Diabetic neuropathy is a common complication of diabetes mellitus that impairs peripheral circulation and increases the risk of foot ulcers and eventual amputation. Non-pharmacological interventions such as diabetic foot exercises and warm water foot soaks have not yet been fully optimized in nursing practice, despite their potential to improve peripheral circulation. This case report aimed to evaluate the effectiveness of combining diabetic foot exercises with warm water foot soaks in enhancing peripheral circulation and reducing blood glucose levels in a patient with diabetic neuropathy. The study employed a descriptive design based on the nursing process, involving a 73-year-old female patient diagnosed with Type 2 Diabetes Mellitus and diabetic neuropathy. The combined intervention consisted of 15–20 minutes of diabetic foot exercises followed by a 15-minute warm water foot soak at a temperature of 37–40°C. The intervention was administered daily for seven consecutive days. Evaluation measures included the Ankle–Brachial Index (ABI) and daily blood glucose monitoring. The results demonstrated an improvement in the ABI value from 0.60 to 1.02, indicating enhanced peripheral circulation, progressing from moderate Peripheral Arterial Disease to a borderline normal category. Blood glucose levels decreased from 381 mg/dL to 189 mg/dL. It should be noted that the patient began taking acarbose 100 mg on the sixth and seventh days, obtained from a community health post (Posyandu). No adverse effects were observed during the intervention period. In conclusion, the combination of diabetic foot exercises and warm water foot soaks improved peripheral circulation and supported glycemic control in a patient with diabetic neuropathy, suggesting that this approach may serve as a safe and practical self-care therapy modality.